CONVULSIVE DISORDER IN CHILDREN: THE ROLE OF HERPES VIRUS INFECTIONS - L. V. Vashura; M. S. Savenkova; N. N. Zavadenko; I. E. Koltunov; N. V. Carazhas; T. N. Rybalkina; M. Yu. Kalugina; A. V. Bullih (Детские инфекции (Москва))
Convulsive disorder frequently poses a great danger. The authors distinguish three groups of children who most often have convulsions. Those are «febrile» convulsions, convulsions that accomapny neuroinfections and epilepsy. Male gender and age under 1 year are early predictors of «Febrile» convulsions. Convulsions accompanying neuroinfections and epilepsy manifest later. In 64,6 % of the children the main role belongs to herpesviruses, especially from the group of CMV and G6 type. When a child with convulsions is accepted to in-patient hospital, a complex comprehensive examination (ELISA and PCR ) must be carried out to ensure timely diagnosis and treatment.